2015
DOI: 10.1007/s11695-015-1907-0
|View full text |Cite
|
Sign up to set email alerts
|

Increased Prevalence of Irritable Bowel Syndrome in a Cohort of French Morbidly Obese Patients Candidate for Bariatric Surgery

Abstract: Thirty percent of obese patients had IBS: its severity was not correlated with BMI. However, anxiety was independently associated with IBS, suggesting that psychological factors are key features of IBS, whatever the presence of obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
31
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 27 publications
7
31
1
2
Order By: Relevance
“…The association between IBS and self-reported psychiatric disorders is in accordance with studies in patients with morbid obesity and in the general population [7, 8, 14], patients with morbid obesity are known to have higher levels of stress, anxiety, and depression [15]. Associations between IBS and vitamin B 6 deficiency [18, 19] and low-grade systemic inflammation measured as CRP [16, 17] were not seen in this study.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The association between IBS and self-reported psychiatric disorders is in accordance with studies in patients with morbid obesity and in the general population [7, 8, 14], patients with morbid obesity are known to have higher levels of stress, anxiety, and depression [15]. Associations between IBS and vitamin B 6 deficiency [18, 19] and low-grade systemic inflammation measured as CRP [16, 17] were not seen in this study.…”
Section: Discussionsupporting
confidence: 88%
“…At IHT-G, the prevalence (27%) was three-fold that in the general population from the same region [14]. A high prevalence of IBS is consistent with most other reports from obesity centres [810]. …”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…1,4,9 Animal studies have demonstrated the influence of stress on colonic permeability, and mucosal and systemic inflammation's mediation by the autonomic nervous system and the hypothalamo-pituitary-adrenal axis. 4 Several recently published studies have mapped IBS's relationship with psychological disorders [10][11][12][13][14][15][16] and compared depression and anxiety levels in IBS-subtypes. 15,17,18 However, the relationship between IBS and psychological disorders (depression or anxiety) was inconsistent, even in a recent meta-analysis entailing eight studies.…”
Section: Introductionmentioning
confidence: 99%